The Creative Economy in Maine - Dobelle, Evan (Maine Policy Review, 2005)
In the Margaret Chase Smith Essay, Evan Dobelle reflects on Maine’s emerging creative economy. He notes the collaboration with the state’s universities and colleges, and points to the importance of developing “creative clusters.”
Keywords: Maine; creative economy